2001
DOI: 10.1186/1472-6890-1-3
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory infiltrate in the acute stage of the dextran sulphate sodium induced colitis: B cell response differs depending on the percentage of DSS used to induce it

Abstract: BackgroundExperimental colitis with features similar to inflammatory bowel disease (IBD) has initially been described. A detailed analysis of inflammatory cells has not yet been described. Therefore in this study we characterized the cells involved in the acute phase of the colitis and compared those findings to what is known about human IBD.MethodsColitis was induced in BALB/C and C57Bl6 mice by ingestion of 2.5% and 5% DSS in the drinking water for 8 days. Cells were labelled by immunohistochemical staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 30 publications
6
51
0
1
Order By: Relevance
“…In the colitis model used in this study, DSS, a sulfated polymer, induces intestinal injury by a direct toxic effect on epithelial cells of the basal crypt, with a loss of integrity in the mucosal barrier allowing infiltration of intestinal bacteria (21). Subsequently, colon inflammation develops with an infiltration of macrophages, neutrophils, and eosinophils into the colon and increased production of the inflammatory cytokines IL-1b, TNF-a, and IL-6, which contribute to the inflammation and damage to the colon (21,31). In this study, the severity of all DSS-induced pathology was significantly reduced in SIGN-R1 2/2 mice relative to wild-type animals, suggesting that recognition of bacterial surface carbohydrates by SIGN-R1 may contribute to the development of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the colitis model used in this study, DSS, a sulfated polymer, induces intestinal injury by a direct toxic effect on epithelial cells of the basal crypt, with a loss of integrity in the mucosal barrier allowing infiltration of intestinal bacteria (21). Subsequently, colon inflammation develops with an infiltration of macrophages, neutrophils, and eosinophils into the colon and increased production of the inflammatory cytokines IL-1b, TNF-a, and IL-6, which contribute to the inflammation and damage to the colon (21,31). In this study, the severity of all DSS-induced pathology was significantly reduced in SIGN-R1 2/2 mice relative to wild-type animals, suggesting that recognition of bacterial surface carbohydrates by SIGN-R1 may contribute to the development of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have implicated a role for B cells during DSS colitis, yet the true pathological importance of this cell population during experimental colitis remains poorly understood. 58,59 CD11b may be important for B-cell function and/or recruitment. We have recently reported that the loss of CD11b in the MRL/ MpJ-Fas lpr mouse lupus model results in enhanced lymphadenopathy with focal accumulation of plasma and Mott cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to the method by Stevceva et al (28) from 2001, a mouse model of UC was established using dextran sulfate sodium (DSS; MP Biomedicals, Santa Ana, CA, USA). A total of 80 female BALB/c mice were stochastically divided into eight groups and housed in separate cages (10 mice per cage).…”
Section: Animals and Colitis Modelingmentioning
confidence: 99%